KAJI EKSPERIMENTAL PERFORMA DAN EMISI GAS BUANG PADA SPARK IGNITION ENGINE DENGAN BAHAN BAKAR BENSIN - Nursofyan Nursofyan; Berkah Fajar TK. (JURNAL TEKNIK MESIN, 2015)
In the national industrial policy, industrial transportation (automotive) is one of the priority sub-sectors to be developed. Development of four-wheeled motor vehicle production are energy efficient and affordable price set out in the Ministerial Decree No. 33 / M-IND / PER / 7/2013. Permenperin is a derivative of a low carbon emission car program or low emission of carbon (LEC) which has been stipulated in Government Regulation No. 41 of 2013. The development of automotive technology leads to improved engine performance and decrease harmful exhaust emissions. The purpose of this thesis is to determine the performance of spark ignition engines, knowing the exhaust emissions of spark ignition engines, manual measurement and measurement verification using data acquisition. The research method is a literature review of the literature that is tailored to the development of technology and based on national and international standards. Technically, this research begins with the study of literature and discussion of the results of research and literature that already exists. The output of this research can be used as a reference for the training and development of new and renewable energy sources and environmentally friendly transport sector.